Chapter 10: SCIAMACHY's View of the Changing Earth's Atmosphere - Bovensmann, Heinrich; Aben, Ilse; Van Roozendael, Michel; Kühl, Sven; Gottwald, Manfred; von Savigny, Christian; Buchwitz, Michael; Richter, Andreas; Frankenberg, Christian; Stammes, Piet; de Graaf, Martin; Wittrock, Folkard; et al. (Springer Dordrecht Heidelberg London New York, 2011)
Since August 2002 SCIAMACHY delivers a wealth of high-quality data permitting to study the status of the Earth’s atmosphere. Enhanced concentrations of greenhouse gases are identified as the major source of global warming and their atmospheric concentrations are increasing. SCIAMACHY monitors the most prominent species such as CO2, CH4 and water vapour, the latter including isotope variants. Further anthropogenic impacts on the troposphere occur by emission of reactive trace gases contributing to pollution and affecting air quality. With SCIAMACHY their global, regional and even local signatures can be detected. Long-term analyses document how the emissions of NO2, SO2, HCHO, CHOCHO and CO evolve with time. In addition, the halogen cycle of polar BrO and IO, both of natural origin, is studied. The stratosphere is the layer where public interest in the Earth’s atmosphere has begun to grow with the detection of the ozone hole in the mid-1980’s. Until the mid-1990s a steady decrease has been observed in the ozone abundance. The most striking feature is the massive loss of stratospheric ozone over Antarctica during each southern spring. In order to detect possible signs of recovery, SCIAMACHY contributes to the continuous monitoring of the ozone layer, the ozone hole, Polar Stratospheric Clouds (PSC) and species impacting the ozone chemistry such as NO2, OClO and BrO. A much more poorly explored region is the mesosphere and lower thermosphere, which forms the transition between interplanetary space and the terrestrial atmosphere. This region is dominated by extraterrestrial impacts as well as couplings to the lower atmosphere. With SCIAMACHY’s limb viewing capabilities Noctilucent Clouds (NLC) are studied providing insight into generation and depletion mechanisms. At times of strong solar activity, SCIAMACHY measurements reveal how the chemistry of the upper atmosphere is disturbed. By analysis of emission lines in SCIAMACHY spectra the composition of the thermosphere above 100 km can be studied. SCIAMACHY is the ...